Повзучість внутрішнього корпусу циліндра високого тиску парової турбіни К-325-23,5 - Гонтаровський, Павло Петрович; Шульженко, Микола Григорович; Гармаш, Наталія Григорівна; Глядя, Алла Олександрівна (Національний технічний університет "Харківський політехнічний інститут", 2019)
Корпус парової турбіни є одним із найбільш відповідальних і напружених вузлів, на якому безпосередньо відображаються жорсткі умови експлуатації. За допомогою розроблених на основі методу скінченних елементів розрахункової методики й програмного забезпечення, що дозволяють аналізувати термонапружений стан елементів енергомашин з урахуванням конструктивних особливостей і умов навантаження в тривимірній постановці, проведена оцінка повзучості внутрішнього корпусу циліндра високого тиску парової турбіни К-325-23,5. Проведені розрахункові дослідження показали, що в результаті повзучості корпусу напруження перерозподіляються по об'єму, а максимальні деформації повзучості не перевищують 0,31 %. Внутрішній корпус має значний резерв до вичерпання ресурсу.

The body parts are the most critical elements of steam turbines that operate being exposed to the action of the complicated thermal power loads. These parts are not subject to their replacement during the entire period of their operation. The defects are accumulated in them due to the low-cycle fatigue and creepage. For the reliable determination of the thermostressed state of turbine casings we need to solve thermomechanical problems with variable boundary conditions and temperature-dependent material properties. Special FEM (finite element method) – based computation technique and software package were developed to carry out the 3D simulation of the kinetics of thermostressed state peculiar for power equipment elements. The calculation studies were carried out for the thermostressed state of the inner shell of the high-pressure cylinder used by the steam turbine К-325-23.5. To take into account its structural properties the available software was improved through the introduction of the new types of finite elements. The temperature field distribution was derived from the solution of the heat conductivity problems using the boundary heat exchange conditions of a third kind on appropriate surfaces. The creepage was defined by the theory of aging using isochoric steel curves for 200 thousand hours. The obtained data showed that a significant redistribution of equivalent stresses was observed in the high-temperature zone of the casing due to the metal creepage. Maximum equivalent tensile and compressive creepage strains have actually the same level and do not exceed 0.31 % for the given time. It means that the inner shell has a considerable in-service life reserve.
Creepage of the inner shell of the high-pressure cylinder of the steam turbine К-325-23.5
Keywords: термонапружений стан; деформації; thermostressed state; the strains